1981
DOI: 10.1159/000207130
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Platelet-Associated IgG with Competitive Solid-Phase Enzyme Immunoassay

Abstract: In order to measure platelet-associated IgG (PAIgG), we devised a solidphase enzyme immunoassay employing a competitive binding of peroxidase-conjugated anti-IgG antiserum between platelets and polystyrene tubes coated with IgG. The amounts of peroxidase bound to the tubes were measured in a spectrophotometer by an enzymatic reaction. This method is highly sensitive, reproducible and can be carried out more simply. The PAIgG values of normal controls averaged 21.6 ± 6.6 (SD) ng/l0τ platelets. 27 (93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…Intracellular platelet /l-TG and PF4 were determined after ultrasonication of 1 ml PRP (50>< 104/,ul platelets) at 0°C for 30 sec in a 150 watt ultrasonic homogenizes at a wave amplitude 7 kHz. PAIgG was measured by competitive enzyme immunoassay (Tsubakio et al 1981). Glycoprotein of platelet membrane was stained following electrophoresis on SDS polyacrylamide gels (SDS-PAGE ).…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular platelet /l-TG and PF4 were determined after ultrasonication of 1 ml PRP (50>< 104/,ul platelets) at 0°C for 30 sec in a 150 watt ultrasonic homogenizes at a wave amplitude 7 kHz. PAIgG was measured by competitive enzyme immunoassay (Tsubakio et al 1981). Glycoprotein of platelet membrane was stained following electrophoresis on SDS polyacrylamide gels (SDS-PAGE ).…”
Section: Methodsmentioning
confidence: 99%
“…The separation of platelet-rich plasma (PRP) from each patient and normal donor was based on a previously described method [3]. PRP was centri fuged at 1,200 g for 10 min, the cell buttons were sus pended in a small amount of RCD solution [9]; ap proximately 50 gC\ of radioactive chromium (5lCr) was added per sample, followed by 30-min incuba tion at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative assays of platelet-associat ed IgG (PAIgG), including our competi tive solid-phase enzyme immunoassay [3], have been reported and the results indicat ed that in ITP, increased PAIgG correlat ed inversely with both platelet survival [4] and the level of thrombocytopenia [3][4][5][6][7][8]. We thought the PAIgG assay to be the most valuable method for detecting plate let autoantibody in ITP and investigated the relationship between the results ob tained by the direct assay and PAIgG val ues in ITP patients.…”
mentioning
confidence: 99%
“…However, accumulated evidence suggested that normal platelets have two IgG pools, one located on platelet surface (100 IgG molecules) and one intracellular pool (20,000 IgG molecules) [34,35]. Older methods also measured the IgG ofgranules, leading to falsely elevated results for surface IgG [36][37][38]. Surface immunoglobulin was later measured with I131-labeled monoclonal antibody for all IgG subclasses or labeled staphylococcal protein A [39][40][41].…”
Section: Detection Of Antiplatelet Antibodiesmentioning
confidence: 99%